Analysis of Reasons for Filing Underage Marriage Dispensation Post Amendment to The Marriage Law Number 01 of 1974 by Law Number 16 of 2019 - Ihsan, Ihsan; Malarangan, Hilal; Nasaruddin, Nasaruddin (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2023)
The regulation change to the dispensation of marriage following the difference in the limiting age of marriage in Law Number 16 of 2019 is due to concerns over the increasing cases of underage marriages. This study aims to describe the procedures and considerations of judges regarding the reasons for filing a marriage dispensation case at the Tolitoli Religious Court and explain the relevance of maqasid sharia and sociological jurisprudence to the reasons for filing a marriage dispensation at the Tolitoli Religious Court. The research method used is qualitative research with a case study approach as an instrument in the research design and data collection through field research. The results of this research explain that legal considerations and considerations of community justice became the reason for the Tolitoli Religious Court judges when explaining the procedure and the reasons for filing a marriage dispensation case at the Tolitoli Religious Court and realizing protection for children both in terms of benefit and instruments of social change and reducing the prevalence of child marriage in Tolitoli Regency as a form of relevance between maqashid sharia and sociological jurisprudence towards marriage dispensation. The judge's consideration in granting the request for a marriage dispensation, either reviewed through maqashid shariah or sociological jurisprudence, needs to be studied more deeply so that the results of the decision from the application can help to realize a household life that is sakinah, mawaddah, and rahmah because marriage is not only for oneself but also for other people called family.